2008
DOI: 10.1016/s1474-4422(07)70331-9
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and outcome of convulsive status epilepticus in Kenyan children: a cohort study

Abstract: SummaryBackgroundConvulsive status epilepticus (CSE) is the most common neurological emergency in childhood and is often associated with fever. In sub-Saharan Africa, the high incidence of febrile illnesses might influence the incidence and outcome of CSE. We aimed to provide data on the incidence, causes, and outcomes of childhood CSE in this region.MethodsBetween March, 2006, and June, 2006, we studied all children who had been admitted with CSE to a Kenyan rural district hospital in 2002 and 2003. Confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
135
5
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(156 citation statements)
references
References 33 publications
12
135
5
4
Order By: Relevance
“…The hospital-based cohort study carried out in Kenya reported a minimum incidence of 35/100,000/year in children between the ages of 0-13 year [16]. This is referred to as the minimum incidence since a proportion of the children with SE will die before reaching the hospital, and others will be treated in private hospitals [10,16]. The incidence of convulsive status epilepticus in London, UK, has been reported as 18-20 per 100,000 per year in children less than 16 years old [17].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The hospital-based cohort study carried out in Kenya reported a minimum incidence of 35/100,000/year in children between the ages of 0-13 year [16]. This is referred to as the minimum incidence since a proportion of the children with SE will die before reaching the hospital, and others will be treated in private hospitals [10,16]. The incidence of convulsive status epilepticus in London, UK, has been reported as 18-20 per 100,000 per year in children less than 16 years old [17].…”
Section: Introductionmentioning
confidence: 99%
“…A hospitalbased study involving 22 states in the United States of America 4 reported a prevalence of 0.083 percent. The incidence of SE in SubSahara Africa is higher and this may be due to the presence of malaria and other CNS infections, and late presentation in the hospital for treatment when children have fever or are convulsing [8,10,16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations